Pentingnya Pendidikan dan Pelatihan Pembuatan Perjanjian Kerja Bersama (PKB) pada Serikat Pekerja Seluruh Indonesia (SPSI) Kabupaten Banyumas - Sri Wahyu Handayani (MIH Unsoed, 2017)
Labor unions are workers association organizations that will fight for workers' rights when dealing with entrepreneurs. However, based on previous research, labor unions in Banyumas District experienced